Relação neutrófilo/linfócito como ferramenta prognóstica em pacientes com câncer de mama - Faria, Sara Socorro (2016)
Introduction: Breast cancer is an important public health problem because it is the most frequent in women and the one with the highest mortality rate. Early detection of this neoplasm is important for treatment and one of the key factors for its prognosis is the presence of metastases to the axillary lymph nodes. The discovery of new molecular and immunological markers, as tools in the diagnosis, prognosis and treatment of cancer, is of extreme importance. Chronic inflammation is involved in all stages of carcinogenesis. Aims: The present study aimed to estimate overall survival in five and ten years as a function of neutrophil to lymphocyte ratio in patients submitted to mastectomy or quadrantectomy, from 1995 to 2004. Methods: Patients with breast cancer enrolled in the Hospital Araujo Jorge, Goiania, Goias, diagnosed between 1/1/1995 and 12/31/2004. Results: 1290 patients were included in the study. Patients who presented RNL <1.415 had better survival (54.55%), when compared to those with RNL>3.175 (35.46%). Patients with triple-negative carcinoma and with NLR>3.175 had worse overall survival in five years (p = 0.002). In the multivariate analysis, age at diagnosis, compromised lymph nodes, staging (N), neutrophil to lymphocyte ratio and lymphocyte to monocyte ratio were the independent prognostic variables in the survival of this cohort of patients. Conclusion: Overall survival in 10 years, with cases diagnosed in the period between 1995 and 2004, according to the neutrophil to lymphocyte ratio (NLR<1.415) was 54.55% and for NLR>3.175, 35.46%.These results indicate a potential role of circulating inflammatory and immunological cells as potential prognostic markers in this population.